Online Lectures Using Zoom Application For Undergraduate Students During Covid-19 Pandemic Period - Siska Oktaviani (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
This research aimed to obtain information about online learning using the Zoom application for the PGSD students of FKIP of Widya Gama Mahakam University of Samarinda during the Covid-19 pandemic. This research used a qualitative descriptive approach. This research subjects were PGSD students who actively participated in online lectures and selected nine sources, namely four students of class 2018 and five students of class 2019. The selection of these sources used a purposive sampling method. Data collection techniques used were observation, interviews via Zoom meeting and WhatsApp, also documentation. The activities in analyzing the data obtained are data reduction, data presentation, drawing-conclusions, and verification. This research used triangulation techniques to test the validity of the data. It can be concluded from the results of this research that lecturers and students as users of the Zoom application need to understand the steps of using the Zoom application to make it easier to take online lectures. The Zoom application is quite effective as a medium for online lectures because it has effectiveness in terms of place, time, services, and facilities, even though there are also obstacles in its use.